If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + ln(27x) = 24 + -2ln(x) Remove parenthesis around (27x) 6 + ln * 27x = 24 + -2ln(x) Reorder the terms for easier multiplication: 6 + 27ln * x = 24 + -2ln(x) Multiply ln * x 6 + 27lnx = 24 + -2ln(x) Multiply ln * x 6 + 27lnx = 24 + -2lnx Solving 6 + 27lnx = 24 + -2lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '2lnx' to each side of the equation. 6 + 27lnx + 2lnx = 24 + -2lnx + 2lnx Combine like terms: 27lnx + 2lnx = 29lnx 6 + 29lnx = 24 + -2lnx + 2lnx Combine like terms: -2lnx + 2lnx = 0 6 + 29lnx = 24 + 0 6 + 29lnx = 24 Add '-6' to each side of the equation. 6 + -6 + 29lnx = 24 + -6 Combine like terms: 6 + -6 = 0 0 + 29lnx = 24 + -6 29lnx = 24 + -6 Combine like terms: 24 + -6 = 18 29lnx = 18 Divide each side by '29nx'. l = 0.6206896552n-1x-1 Simplifying l = 0.6206896552n-1x-1
| 9ln(x+3)-5lnx= | | 4n=n-4 | | ln(x+1)+ln(x-4)=ln(x+3) | | 8x+10y-22= | | 24-6m= | | -10x-50= | | 30y+8=158 | | (1+y^2)dx=xdy | | 3(x+2)=2x-t | | y=45.307ln(x)+9.5574 | | 36=5x+2 | | 3h=152 | | 49x^2+36=(7x-6)(7x-6) | | (1+y^2)*dx+(1+y^2)*dy=0 | | -5(x+3)=3x-39 | | (1+y^2)dx+(1+y^2)dy=0 | | -5=4v+7 | | (xy^2+4x)dx+(y-x^2y)dy=0 | | 5*x=24+x | | x+4(x+3)=12 | | 5*5+8.5*8.5=x^2 | | P=2(b+1) | | -x-21=3x-5 | | (x+1)4-6x=-4x-10 | | 2x(7x+5)=13-3x | | 2x(7x+5)=13-3 | | lnx=0.67 | | 0.4x^2=0.1x | | X^2+5=x(2x+5) | | f(x)=4x^4+6x^3-11x^2+20 | | 2(v+8)=4v+32 | | (x+5)(x-5)(x+2)(x-2)(x+2i)(x-2i)= |